Remembering 1965: Indonesian cinema and the 'Battle for History' - ESPENA Darlene Machell (Institutional Knowledge at Singapore Management University, 2017)
Using four films to probe the transformations in Indonesia’s historical memory, this paper examines how the Indonesian society remembers, interrogates, and comes to terms with one of their nation’s most traumatic episodes: the widespread communist purge that followed the failed coup on 30 September 1965. It also demonstrates how they reflect various perspectives on the 1965 killings that are—to an extent—part of the “Battle of History” (van Klinken 2001) in postSuharto Indonesia, wherein different historiographic traditions introduce new actors, reveal the nuances, and challenge longstanding dominant understandings of 1965.